PEMANFAATAN MEDIA PAPAN KOTAK DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI SATUAN BERAT KELAS 2 MIN 2 BANGKALAN - Maulidina Tamalla; Agung Setyawan (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2023)
Based on initial data in class 2 MIN 2 Bangkalan, problems were found in learning mathematics in the unit weight material, namely students' lack of understanding due to the absence of learning media, so students were not active, bored and did not even master the material. This factor resulted in low student learning outcomes. By applying a gridboard learning media is an alternative solution to overcome problems in learning mathematics unit weight class 2 MIN 2 Bangkalan. The purpose of this study was to find out 1) the process of using square board media in mathematics lessons on weight units and 2) improving student learning outcomes on weight unit material through the use of square board media. The type of research used is classroom action research (CAR), which has 2 cycles. Each cycle consists of planning, implementing, observing and reflecting. The research location was MIN 2 Bangkalan, Labang District, Bangakalan Regency which was conducted from February to March 2023. The research used a quantitative approach. Data collection techniques used are tests, observation and documentation. The research instrument was in the form of student learning outcomes test sheets. The subjects of the study were all 2nd grade students for the 2022/2023 academic year, totaling 28 students, consisting of 12 male students and 16 female students. Journal homepage: https://ejurnal.univamedan.ac.id/index.php/jkpm/index The results showed that the use of blackboard media can improve student learning outcomes that achieve scores above KKM (76) with a percentage of complete learning outcomes, pre-cycle 39.29% with an average score of 66.4, Cycle I 57.14% with an average score of 76 and Cycle 2 100% with an average of 90. Based on the research it can be concluded that learning mathematics in units of weight with the use of media unit weight boxes can be successful, so that it can be used as an alternative solution to improve mathematics learning in MIN 2 Bangkalan